Main Factors Affected by the Threat of Extinction and Damage to the Betawi Language for Society - Arju Susanto; Zeffry Alkatiri (LingLit Journal Scientific Journal for Linguistics and Literature, 2022)
The Betawi language, like other languages in the world, is in danger of extinction caused by many things, including the dynamics of civilization. This situation threatens many contexts of indigenous Betawi culture and civilization. Therefore, the maintenance and preservation of the Betawi language is a necessity that must be carried out. The problem is the breadth of the Betawi text and linguistic context. For this reason, it is necessary to formulate an approach strategy that is more focused on what are the main factors that must be studied from the impact of damage and the endangerment of the Betawi language on the Betawi people themselves. This study formulates these factors by conducting research and field testing for more than 1 year of intensive observation 24 hours a day. Sociological qualitative analysis in particular observing the social assessment of society is the most effective method found during this research process. As a result, at least 5 segments were found that must be studied to see the impact of damage and the endangerment of the Betawi language, namely linguistic factors, personal identity, communication between generations, transfer of knowledge and knowledge, and economics.